Serum concentration of aminotranferases in guinea pigs (Cavia porcellus) fed diets based on pisonay (Erythrina sp) - Ramirez-Borda, Yony (2019)
The experiment was carried out in Tamburco, province of Abancay, Peru with the objective of determining the effect of diets based on pisonay (Erythrina sp) on the concentration of tannins and total alkaloids, the serum concentration of the aminotransferases, the lesions in the liver and the liver/liveweight ratio of the guinea pigs. Leaves and petioles of pisonay were used with four months of regrowth and fresh alfalfa (Medicago sativa) with 28 days of regrowth in the diet of 24 improved male guinea pigs, distributed in three treatments: diet A100: 100% alfalfa (80 g), diet A50P50: 50% alfalfa (40 g) plus 50% pisonay (40 g) and diet P100: 100% pisonay (80 g). The feeds were supplied twice a day. Serum levels and liver/liveweight ratio were analysed with complete random design, the effect of diets on guinea pig liver lesions was analysed with Fisher's exact test. The concentration of tannins in the pisonay (14.0 g/kg DM) was higher than those found in alfalfa (2.2 g/kg DM). No total alkaloids were detected in the alfalfa. Serum levels of alanine aminotransferase (ALT) in guinea pigs fed A100 (39.1 ± 7.2 IU/L), A50P50 (48.8 ± 7.1 IU/L) and P100 (62.0 ± 8.4 IU/L) showed significant differences (p<0.05). Aspartate aminotransferase (AST) in guinea pigs fed A50P50 (71.9 ± 15.2 IU/L) and P100 (76.4 ± 11.8 IU/L) were higher than animals fed A100 (p<0.05). The increase of 50 to 100% of pisonay in the diet of guinea pigs produces lesions in the liver such as fatty degeneration and necrotic foci, in addition to decreasing the liver/liveweight ratio. The pisonay and fresh forage in 50 and 100% in the diet of guinea pigs can adversely affect the health of the animals.